Effect of Crossing Period on Seed Germination and Seedling Vigour of Cotton Hybrid DHH-543 - S.R. DODDAGOUDAR; M. SHEKHARGOUDA; B.M. KHADI; M.R. ESHANNA; N.K. BIRADARPATIL; H.M. VAMADEVAIAH (Seed Research, 2026)
The influence of five crossing period viz., first crossing period to last crossing period (C₁-C5) each with fifteen days interval were studied for seed quality parameters. The seeds obtained from the bolls set at first three crossing periods (C1, C2, C3) gave higher seed index, germination percentage, shoot length, seedling dry weight and seedling vigour index as compared to those seeds obtained from the later crossed bolls (C, and C5). However, the germination percentage even in fourth and fifth crossing periods recorded above minimum seed certification standards (75%). Hence, the seeds obtained from all the five fortnight crossings periods in DHH-543 intra-hirsutum hybrid seed production can be used as seed for commercial sowing.